1957
DOI: 10.1042/bj0660468
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid sequence in a fraction of the fibroin of Bombyx mori

Abstract: 1. Methyl-O-fl-D-fructofuranoside has been prepared by the action of yeast invertase on sucrose in the presence of methanol. 2. The fructoside has been used as a substrate for a mould-enzyme preparation (Taka-diastase). An examination of the products showed that both hydrolysis and transfructosylation occurred. 3. Sucrose could not be detected among the products of action upon mixtures of methyl ,Bfructoside and glucose, either by chromatographic fractionation or by the use of 14C-labelled glucose. 4. Taka-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…5 Thus we had to use ␣-chymotrypsin because the ␣-chymotrypsin preferentially catalyzes the hydrolysis of peptide bonds at the carboxyl groups of tyrosine, and is very useful for hydrolyzing silk fibroins containing about 5% tyrosine by weight. 6 Furthermore, it was previously reported that the acylation of protein can be performed completely with the use of ␣-chymotrypsin. 7 The resulting monomer was confirmed by the change of solubility in the good solvent for SFP and that of UV-visible spectra of SFP before and after acylation.…”
Section: Preparation Of Sfp Monomermentioning
confidence: 99%
“…5 Thus we had to use ␣-chymotrypsin because the ␣-chymotrypsin preferentially catalyzes the hydrolysis of peptide bonds at the carboxyl groups of tyrosine, and is very useful for hydrolyzing silk fibroins containing about 5% tyrosine by weight. 6 Furthermore, it was previously reported that the acylation of protein can be performed completely with the use of ␣-chymotrypsin. 7 The resulting monomer was confirmed by the change of solubility in the good solvent for SFP and that of UV-visible spectra of SFP before and after acylation.…”
Section: Preparation Of Sfp Monomermentioning
confidence: 99%
“…A closer examination shows that over 20°/, of the sequence takes the form of two runs of (Gly-X),. This arrangement is reminiscent of the structure of Bombyx mori silk fibroin [20].…”
Section: Trp-pro-phementioning
confidence: 99%
“…In the early 1950s, Lucas et al 7 used acid hydrolysis followed by ion-exchange chromatography to separate and identify the amino acids. These workers characterized the amino acid composition of both sericin and fibroin of Bombyx mori and Antheraea silks.…”
Section: Introductionmentioning
confidence: 99%